Effects of biofeedback on biomechanical factors associated with chronic ankle instability: a systematic review with meta-analysis - Seyed Hamed Mousavi; Fateme Khorramroo; Hooman Minoonejad; Johannes Zwerver (BMC, 2023)
Abstract Background Biofeedback may alter the biomechanics of lower extremities in patients with chronic ankle instability (CAI). We aimed to systematically review the literature on the effect of gait-training and biofeedback on biomechanical parameters in individuals with CAI and conduct a meta-analysis. Methods We searched four databases including PubMed, Web of Science, Scopus and Embase from their inception through 30th June 2022. The Downs and Black appraisal scale was applied to assess quality of included studies. Two reviewers screened studies to identify those reporting the effect of biofeedback on biomechanical factors associated with CAI. Outcomes of interest were kinetics and kinematics. Two authors separately extracted data from included studies. Data of interest were study design, number of sessions, intervention, tools, outcomes, number, sex, age, height, and body mass of participants. Results Thirteen studies with a total of 226 participants were included. Biofeedback was capable of shifting center of pressure (COP) and lateral plantar pressure medially and reducing foot inversion, adduction, propulsive vertical ground reaction force (vGRF), ankle joint contact force, peak pressure and pressure time integral in the lateral mid-foot and forefoot. Auditory biofeedback had agreater impact on modifying plantar pressure in individuals with CAI. The meta-analyses revealed that visual biofeedback reduces peak pressure in lateral mid-foot and pressure time integral at lateral and medial heel and pressure increases under the hallux. Conclusion Biofeedback can alter pressure, vGRF, and foot inversion associated with CAI. Auditory biofeedback had greater impact on modifying plantar pressure in individuals with CAI. Further studies are required to assess the prolonged effect and clinical consequences of biofeedback or a combination of feedback on CAI in different age groups. Moreover, developing a low-cost and user-friendly device that can be evaluated in high quality RCTs is important prior to implementing the intervention in the clinical setting to reduce symptoms of CAI.